Evaluasi Komprehensif Kualitas Briket dari Arang Tempurung Kelapa dan Campuran Serbuk Gergaji Sengon Terkarbonisasi/Tidak Terkarbonisasi - Dimas Ficky Hidayat; Yeyen Maryani; Eka Sari (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
This study comprehensively evaluates the quality of biomass briquettes produced from blends of coconut shell charcoal and sengon sawdust, using both carbonized and non-carbonized materials. Composite briquettes were fabricated with varying compositions and characterized through proximate analysis, calorific value, density, and burning rate measurements to determine their suitability as solid fuel. The results indicate that adding non-carbonized sawdust increases volatile matter content and burning rate but reduces the calorific value of the briquettes. In contrast, incorporating up to 10% carbonized sawdust significantly improves the calorific value to 6119.2 cal/g, approaching that of pure coconut shell charcoal (6352.2 cal/g), while maintaining a relatively high burning rate. Briquettes containing carbonized sawdust also exhibit low ash content, below 3%, and moisture content under 8%, meeting standard solid fuel quality requirements. These findings demonstrate that a strategic combination of carbonized and non-carbonized materials can produce hybrid biomass briquettes with optimized thermal performance, providing a promising, sustainable, and environmentally friendly alternative fuel for domestic and industrial applications.